Early Onset Clean Intermittent Catheterization May Decrease Prevalence and Severity of Urinary Concentration Defects in Myelomeningocele Patients with Neurogenic Bladder: A Retrospective Cohort Study - Ebrahimnejad, Mohsen; Ghahestani, Seyyed Mohammad (Urology Journal, 2023)
Purpose: Myelomeningocele is the most severe form of spina bifida. Management of urologic consequences of spina bifida is life long, demanding and costly for both the patient and the public health system. There is a paucity of data in the literature regarding concentration defects and their consequences on this disease. This paper aims to describe retrospectively the effect of early onset clean intermittent catheterization (CIC) in on the severity of urinary concentration defects in myelomeningocele patients with neurogenic bladder in a retrospective observational study. Materials and Methods: In this 10-year retrospective cohort study, children with myelomeningocele were selected with the Convenience sampling method. Demographic characteristics, polyuria index ratio (PIR) defined as 24 hour urine output of each patient divided by the maximum normal urine output of the same patient in a healthy state, and nocturnal polyuria index (NPI) were compared between early starters (< 2 years old) or late starters (≥ 2 years old) groups. Results: Seven patients who underwent cystoplasty were excluded and 130 patients (63.8% male, 5.4 ± 3.2 years old, 14.3 ± 2.83 Kg, 28.5% early onset CIC) were investigated. PIR > 1 in inset (1.7 ± 0.2 vs. 2.2 ± 0.5, P = 0.021) and outset (1.5 ± 0.32 vs. 2.5 ± 0.7, P = 0.004) were lower in early starters group than in late starters group. NPI in inset (0.2 ± 0.007 vs. 0.32 ± 0.10, P = 0.018) and outset (0.25 ± 0.15 vs. 0.42 ± 0.095, P = 0.007) were also lower in the early starters group. No further adverse events were reported during the follow-up period. Conclusion: Early onset CIC is more effective than late-onset CIC in preserving the urinary ability of kidneys in myelomeningocele patients.